Les artefacts en os et bois de cerf à Bukovac, Lokve (Croatie)Une seconde flûte possible ? Relations entre les chasseurs de Lokve et les montagnardsd’Olcheva au début du Paléolithique supérieur - Zoltán Horusitzky, François (Arheološki vestnik, 2004)
The possibility of another “flute” at the Bukovac cave nearLokve. Discussion of the famous rib of three holes with a clearcontra-lateral biting by animal tooth. Mysterious, entirely clo-sed cave bear radius with a man-made hole. Reconstructionand acoustical study of two preforated juvenile cave bear fe-murs. It will be shown that the well known spearhead couldhave been a split-base point. Discussion of analogies and chro-nology of bone and antler points with split-base and massivebase. Equal resistance evaluation of the points and their evo-lution in the Early Upper Palaeolithic. Comparison of the Bukovacspearhead with similar points. Discussion of the “Olschewian”concept by Bayer. Relations between the cultural center of Olševaand the secondary hunting stations of Bukovac, Badl-höhle,Salzofenhöhle etc. Parallel evolution in Aurignac.